The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1371/journal.pone.0187985
|View full text |Cite
|
Sign up to set email alerts
|

Reduced starch granule number per chloroplast in the dpe2/phs1 mutant is dependent on initiation of starch degradation

Abstract: An Arabidopsis double knock-out mutant lacking cytosolic disproportionating enzyme 2 (DPE2) and the plastidial phosphorylase (PHS1) revealed a dwarf-growth phenotype, reduced starch content, an uneven distribution of starch within the plant rosette, and a reduced number of starch granules per chloroplast under standard growth conditions. In contrast, the wild type contained 5–7 starch granules per chloroplast. Mature and old leaves of the double mutant were essentially starch free and showed plastidial disinte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…However, s ex1-8 did not reveal a reduced starch granule number per chloroplast ( Mahlow et al, 2014 ). Similarly, dpe2/phs1/sex1-8 revealed 5-7 starch granules even when plants were grown at 12 h light and 12 h dark conditions ( Malinova and Fettke, 2017 ). Thus, it was concluded that ongoing starch degradation is essential for the observed reduced number of starch granules in dpe2/phs1 ( Malinova and Fettke, 2017 ).…”
Section: Additional Proteins Influencing the Starch Granule Numbermentioning
confidence: 99%
See 2 more Smart Citations
“…However, s ex1-8 did not reveal a reduced starch granule number per chloroplast ( Mahlow et al, 2014 ). Similarly, dpe2/phs1/sex1-8 revealed 5-7 starch granules even when plants were grown at 12 h light and 12 h dark conditions ( Malinova and Fettke, 2017 ). Thus, it was concluded that ongoing starch degradation is essential for the observed reduced number of starch granules in dpe2/phs1 ( Malinova and Fettke, 2017 ).…”
Section: Additional Proteins Influencing the Starch Granule Numbermentioning
confidence: 99%
“…In agreement with the observed binding of longer soluble maltodextrins by PTST2, it could be speculated that soluble maltodextrins longer than DP10 are involved in the starch granule initiation, as in dpe2/phs1 no limitation for maltodextrins shorter than DP10 were observed ( Malinova et al, 2014 ). Similarly, when in the background of dpe2/phs1 the starch degradation was blocked by the additional lack of GWD, this glucan balance was again influenced and resulted in an increased number of starch granules with 5-7 granules per chloroplast similar to wild type ( Malinova and Fettke, 2017 ). However, the additional lack of GWD in ss4 has no effect on the starch granule number ( Crumpton-Taylor et al, 2013 ).…”
Section: Metabolic Implications Of Variability In Starch Granule Numbmentioning
confidence: 99%
See 1 more Smart Citation
“…The granules extracted from wild-type Arabidopsis leaves were 338 lenticular in shape with a smooth surface. Several mutations affecting Arabidopsis starch-339 metabolizing enzymes were reported to affect starch granule morphology (Szydlowski et al, 340 2011;Malinova & Fettke, 2017). This is also the case of the ss4 mutants that accumulate 341 large and spherical granules with a smooth surface.…”
Section: Selection Of Pii1 Lines 252mentioning
confidence: 99%
“…The granules extracted from WT Arabidopsis leaves were lenticular in shape with a smooth surface. Several mutations affecting Arabidopsis starch‐metabolizing enzymes were reported to affect starch granule morphology (Szydlowski et al ., ; Malinova & Fettke, ). This is also the case of the ss4 mutants that accumulate large and spherical granules with a smooth surface.…”
Section: Resultsmentioning
confidence: 99%